1980
DOI: 10.1016/0304-3940(80)90153-6
|View full text |Cite
|
Sign up to set email alerts
|

Guitarfish possess ipsilateral as well as contralateral retinofugal projections

Abstract: Autoradiographic analysis of the primary retinal projections in the thornback guitarfish reveals both contralateral and ipsilateral projections to diencephalic, pretectal, and tegmental nuclei and the optic tectum. A total of 12 retino-recipient cell groups receive ipsilateral as well as contralateral inputs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Except for the telencephalic projections, all retinal recipient areas were bilateral, but projections were heavier contralaterally in most target areas. The results coincide basically with those in Acipenser gülden-städti [Repérant et al, 1982], Polypterus palmas, Lepisosteus osseus [Braford and Northcutt, 1983], Lepisosteus platyrhincus [Collin and Northcutt, 1995], Amia calva [Butler and Northcutt, 1992], and Platyrhinoidis triseriata [Northcutt and Wathey, 1980], Lamperta fluviatilis [Vesselkin et al, 1980], Eptatretus burgeri [Kusunoki and Amemiya, 1983], Eptatretus stouti [Wicht and Northcutt, 1990], European Salamandridae [Salamandra salamandra, Triturus cristatus and Triturus alpestris ;Fritzsch, 1980], Ichthyophis kohtaoensis [Himstedt and Manteuffel, 1985], and Bufo marinus [Wye-Dvorak et al, 1992] in that a part of the optic nerve does not decussate at the chiasm, and reaches the ipsilateral target areas. However, Braford and Northcutt [1983] reported that projections to the accessory optic nucleus in Polypterus palmas and Lepisosteus osseus, and to the ventrolateral thalamic nucleus and superficial pretectal nucleus in Lepisosteus osseus are only contralateral.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Except for the telencephalic projections, all retinal recipient areas were bilateral, but projections were heavier contralaterally in most target areas. The results coincide basically with those in Acipenser gülden-städti [Repérant et al, 1982], Polypterus palmas, Lepisosteus osseus [Braford and Northcutt, 1983], Lepisosteus platyrhincus [Collin and Northcutt, 1995], Amia calva [Butler and Northcutt, 1992], and Platyrhinoidis triseriata [Northcutt and Wathey, 1980], Lamperta fluviatilis [Vesselkin et al, 1980], Eptatretus burgeri [Kusunoki and Amemiya, 1983], Eptatretus stouti [Wicht and Northcutt, 1990], European Salamandridae [Salamandra salamandra, Triturus cristatus and Triturus alpestris ;Fritzsch, 1980], Ichthyophis kohtaoensis [Himstedt and Manteuffel, 1985], and Bufo marinus [Wye-Dvorak et al, 1992] in that a part of the optic nerve does not decussate at the chiasm, and reaches the ipsilateral target areas. However, Braford and Northcutt [1983] reported that projections to the accessory optic nucleus in Polypterus palmas and Lepisosteus osseus, and to the ventrolateral thalamic nucleus and superficial pretectal nucleus in Lepisosteus osseus are only contralateral.…”
Section: Discussionsupporting
confidence: 68%
“…We describe the differences by discussing the nomenclature used in previous studies. We also compare the present data with those obtained in four species of chondrichthyans [Nagaprion brevirostris, Graeber and Ebbesson, 1972;Ginglymostoma cirratum, Luiten, 1981a, b; Rhinobatos productus, Ebbesson and Meyer, 1980; Platyrhinoidis triseriata, Northcutt and Wathey, 1980] as well as several teleost species [e.g. Vanegas and Northcutt and Wullimann, 1988;Butler and Saidel, 1991;Ito et al, 1992], lampreys [Vesselkin et al, 1980[Vesselkin et al, , 1984, hagfishes [Kusunoki and Amemiya, 1983;Wicht and Northcutt, 1990], lungfishes [Northcutt, 1977], and amphibians [Fritzsch, 1980;Fritzsch and Himstedt, 1981;Himstedt and Manteuffel, 1985;Uchiyama, 1989;Wye-Dvorak et al, 1992].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…VP: IRP are few in the spiny dogfish, Squalus acanthus [Northcutt, 1979], the spotted dogfish, Scyliorhinus canicula [Repérant et al, 1986], and the shark Hemiscyllium plagiosum [Jen et al, 1983]. In the batoid Platyrhinoidis triseriata, numerous IRP have been demonstrated [Northcutt and Wathey, 1980].…”
Section: Fishes Reptiles and Amphibiansmentioning
confidence: 99%
“…Include four living genera: the dipnoan lungfish (Neoceratodus, Lepidosiren, and Protopterus) and the crossopterygian coelacanth, Latimeria [Nelson, 1984;Carroll, 1988]. VP: In Neoceratodus fosteri, generally considered to be the most primitive of the extant lungfish, IRP has been demonstrated [Moy-Thomas, 1971;Northcutt and Wathey, 1980], while studies in lepidosirenid lungfish have not revealed IRP [Northcutt, 1977;Ward et al, 1995].…”
Section: Lobe-finned Fishesmentioning
confidence: 99%